DEVELOPMENT OF STEM CELL-BASED CANCER THERAPY STRATEGIES - Sumadi; Warda, Rizki Zeillatul (Journal of Stem Cell Research and Tissue Engineering, 2024)
Cancer remains one of the leading causes of death worldwide, with various treatment options available depending on the type and stage of the disease. Traditional therapies, such as surgery, radiotherapy, chemotherapy, and immunotherapy, have shown varying degrees of success, but each has its limitations. Recently, stem cell therapies have emerged as a promising alternative, offering more targeted treatments with fewer side effects. Stem cells, including mesenchymal stem cells (MSCs), induced pluripotent stem cells (iPSCs), and cancer stem cells (CSCs), have demonstrated potential in cancer therapy through mechanisms like tumor site targeting, paracrine signaling, and gene delivery. MSCs, in particular, are of interest due to their ability to migrate to tumor sites and release exosomes that can influence tumor growth, angiogenesis, and metastasis. Modified MSCs have been engineered to deliver anticancer agents or "suicide" genes, providing a more focused approach to tumor treatment. Moreover, MSCs have shown promise in addressing challenges like drug resistance and recurrence in cancer. However, their effectiveness depends on factors such as exosome composition and the tumor microenvironment. Despite the challenges, stem cell-based therapies, including MSC-derived exosomes, represent a novel strategy to enhance the specificity and efficacy of cancer treatments. This review explores current advances in stem cell-based cancer therapies, highlighting their potential, ongoing research, and the need for further studies to optimize these approaches for clinical application.